Photosynthesis-Inhibiting Activity of 1-[(2-Chlorophenyl)carbamoyl]- and 1-[(2-Nitrophenyl)carbamoyl]naphthalen-2-yl Alkylcarbamates - Gonec, Tomas; Stranik, Josef; Pesko, Matus; Kos, Jiri; Oravec, Michal; Kralova, Katarina; Jampilek, Josef (Molecules (Basel, Switzerland), 2017)
Eight 1-[(2-chlorophenyl)carbamoyl]naphthalen-2-yl alkylcarbamates and eight 1-[(2-nitrophenyl)carbamoyl]naphthalen-2-yl alkylcarbamates were tested for their activity related to the inhibition of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. The PET-inhibiting activity of the compounds was relatively low; the corresponding IC50 values ranged from 0.05 to 0.664 mmol/L; and the highest activity within the series of compounds was observed for 1-[(2-chlorophenyl)-carbamoyl]naphthalen-2-yl propylcarbamate. It has been proven that the compounds are PET-inhibitors in photosystem II. Despite rather low PET-inhibiting activities, primary structure-activity trends can be discussed.
Keywords: Structure-Activity Relationship; Photosynthesis; vztahy mezi strukturou a aktivitou; hydroxynaphthalene-carboxamides; Electron Transport; spinach chloroplasts; inhibiční koncentrace 50; Carbamates; structure-activity relationships; transport elektronů; Chloroplasts; karbamáty; Inhibitory Concentration 50; fotosyntéza; PET inhibition; chloroplasty; alkylcarbamates; Spinacia oleracea